A COMPARATIVE STUDY ON ASIA AND EUROPE ON START-UP LED INNOVATIONS AS A VEHICLE FOR DEVELOPMENT: ANY LESSON FOR AFRICA CONTINENTAL FREE TRADE AREA - Otieno, Victor; Muathe, Stephen (American International Journal of Social Science Research, 2022)
This study investigates opportunities that African governments can pursue in furthering their development agenda by leveraging the market's affinity for mobile technology and the momentum built by fintech firms in mobile-based innovation. The study reviews secondary data on innovation-led development initiatives and compares strategies adopted by countries across Europe, Asia, and Africa. The results reveal that Europe and Asia have inculcated structured use of Research and Development in start-up ecosystems to ensure that innovation addresses specific development agendas. In contrast, Africa abounds with high-value natural resources, yet the continent's manufacturing sector is regressing, with intra-Africa trade in consumer goods stagnating at 13% for decades. The study's findings point out that African governments recognize the role start-ups play in addressing unemployment and attendant poverty in Africa. Fintech start-ups and innovators have been at the forefront of delivering financial services using mobile telephony to communities hitherto financially excluded. The success of African mobile money innovations is widely published, and fintech start-ups have attracted the interest of venture capitalists – where 62% of investment funds flowing to start-ups are committed to the fintech sector. There is limited traction in using innovation to address issues like access to potable water, clean energy, affordable healthcare, and quality education.JEL Classification Codes: B17, F13.